(untitled) (European Journal of Formal Sciences and Engineering, 2022)
Transportation and movement of goods is one of the most important human needs, the operation of transportation determines the efficiency of moving products. The progress in techniques and information technology (IT) and management principles improves the moving load, delivery speed, service quality, operation costs, the usage of facilities and energy saving. This study deals with the logistics processes in supply chain management, information technology in management and prospects for the use of information technology in the transportation logistics segment, with particular attention paid to the key factors in information technology that affects the efficiency of transport , allows information to be collected on such as traffic volume, flow, average traffic speed, and actual journey time. Such innovative means of gathering data on automobile traffic open up new perspectives for assessing transport accessibility in terms of automobile traffic by providing high-quality data that meet the requirements for use in company. The main purpose of this study is to give a comprehensive review of information technology (IT) and relationship with transport leading to increased competition and improvement of the level of Algerian companies.